Research on Constructing a Health Management System for Chronic Disease Prevention and Control Based on Tai Chi Intervention - Li, Cuihan; Liu, Mingyu; Xu, Jianan; Liu, Ziyin; Zhang, Peng; Zhang, Jianwei; Lyu, Shaojun (The Journal of the International Society of Chinese Health Practices, 2025)
See PDF for details